Pengaruh Kualitas Produk, Citra Merek. Word Of Mouth, Persepsi Harga Dan Promosi Terhadap Minat Beli Produk Momoyo Di Jember - Dimas Oktriawan Renaldi; Hamzah Fansuri Yusuf; Riza Bahtiar Sulistyan (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study aims to determine the effect of product quality, brand image, word of mouth, price perception, and promotion on purchase interest in momoyo products in Jember Regency. The type of research used is quantitative research. The data used is primary data obtained by distributing questionnaires to momoyo consumers in Jember. The population in this study were all consumers who had purchased momoyo products from the Jember branch, with a sample size of 60 respondents determined using purposive sampling techniques based on certain criteria. The data collection technique used a questionnaire with a Likert scale. The data analysis methods used in this study include validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), and hypothesis testing with the help of IBM SPSS. The results of this study indicate that simultaneously the five independent variables have a significant effect on purchase interest, partially word of mouth and promotion have a significant effect on purchase interest, while product quality, brand image, and price perception do not have a significant effect partially on purchase interest. This finding indicates that word of mouth and promotion strategies have an important role in shaping purchase interest in products, and can be used as a basis for companies in developing targeted marketing strategies